Legal protection of the unborn - Véliz Valencia, Yolange (2024)
At a legal level, the protection of life, considered the most transcendental good for legal subjects, extends from the moment of conception. However, at present, it is a topic that is not given much research attention. The objective of this study was to analyze the legal figure of the conceived from a doctrinal perspective. A qualitative research approach was used, based on bibliographic analysis of various sources to study the proposed problem. The results demonstrate that the defense of life from conception must be imposed from a deontological position, without room for criteria of ambiguity and/or normative vagueness. It is proposed that the protection of the conceived child should be seen as if they were an already born child, due to their defenselessness, which requires the existence of their own legal regulations that protect their survival and allow their existence in the physical.